Collagen peptides promote photoaging skin cell repair by activating the TGF-β/Smad pathway and depressing collagen degradation. Issue 9 (9th September 2019) - Liu, Zehua; Li, Yuqi; Song, Hongdong; He, Juan; Li, Ge; Zheng, Yayao; Li, Bo
Abstract : Collagen hydrolysate has been widely used as a nutraceutical agent against skin aging and has gained increasing attention. Abstract : Collagen hydrolysate has been widely used as a nutraceutical agent against skin aging and has gained increasing attention. Previous research has suggested that oral administration of antioxidant collagen peptides (ACPs) exerted beneficial effects on the photoaging skin structure and collagen. However, the bioactive components in ACP metabolites that are responsible for the repair effects have not been elucidated. In this study, serum containing collagen peptides (CPS) after oral administration and collagen peptides isolated from serum metabolites (SCP) were collected and their effects on cell proliferation, hyaluronic acid secretion and the collagen synthesis pathway in UVA-induced skin fibroblasts (ESF) were evaluated. Furthermore, hydroxyproline (Hyp)-containing collagen peptides from SCP were analyzed and their repair effects were examined. The repair effects of ACP metabolites in serum differed depending on the preparation method and SCP were the active components responsible for the repair effects. SCP displayed repair effects by activating the TGF-β/Smad pathway to promote procollagen synthesis and suppressing AP-1, MMP-1 and MMP-3 protein expression to prevent collagen degradation, in which SHCP exhibited the strongest bioactivity. In addition, SCP showed repair effects by reactive oxygen species (ROS) scavenging activity and preserving the endogenous antioxidant defense systems. Furthermore, IO (Ile-Hyp) and AOG (Ala-Hyp-Gly) were identified as the active peptides promoting procollagen synthesis by activating the TGF-β/Smad3 pathway. These results may be useful in screening of anti-photoaging factors in metabolites and producing highly efficient collagen peptide products.